Do measures of healthy eating differ in survivors of early adversity?. (1st July 2021) - Marquez, Francisco D.; Risica, Patricia M.; Mathis, Karen Jennings; Sullivan, Adam; Gobin, Asi Polly; Tyrka, Audrey R.
Abstract: Early life adversity has been linked to poor health, including obesity. Understanding the role of unhealthy food intake, may elucidate the importance of self-soothing behaviors in explaining the association between early life adversity and poor health in adulthood. The purpose of this study was to assess the association between early life adversity and dietary quality in a sample of adults from the Lifestyle Influences of Family Environment study. Early life adversity, demographic, and dietary data were obtained for 145 participants using formal interviews and two days of interviewer-administered 24-h recalls. Dietary quality was measured using the 2015 Healthy Eating Index (HEI) scoring algorithm to compute total and component scores. The association between early life adversity and dietary quality was assessed through linear regression and in models adjusted for age and sex. The mean ± SD HEI score for all participants was 54.6 ± 12.8. Individuals with early life adversity had a 4.51 lower overall HEI score when compared to those without early life adversity, 95% CI (0.35, 8.68). After adjusting for age and sex, early life adversity was associated with a 4.6 lower HEI score, 95% CI (0.45, 8.73). HEI component scores indicated that individuals with early life adversity were significantly more likely to have lower whole grain (0.7 versus 2.4) and total dairy (4.3 versus 6.1) scores compared to those without early life adversity. ELA was associated with lower measures of dietary quality. Results warrant future research on dietary and behavioral factors that underly the association between early life adversity and poor health outcomes.